Analisis Pengembangan Sumber Daya Manusia pada PT. Surya Artha Nusantara Finance (SANF) - Juhainah - (Indonesian Journal of Islamic Economics and Business, 2022)
The objectives of this research are to identify and explain the implementation of human resource development management in PT. Surya Artha Nusantara Finance along with the performance of human resource development management of PT Surya Artha Nusantara Finance today. The type of research that is used in this research is descriptive research with a qualitative approach. The focus of research is divided into two parts, the first focus is about the implementation of human resource development in PT Surya Artha Nusantara Finance (SANF). The second focus is to know the performance of human resource development in PT Surya Artha Nusantara Finance today. The collection of data by the researcher is based on primary and secondary data. The results and issues evaluation which are undertaken from this research shows the implementation of human resource development SANF is in conformity with the Astra Human Capital Management (AHCM) consisting of Assessing Training Needs, Designing Training Program, Delivery Training, and Training Evaluation. Thecurrent performance of human resource development SANF is going through the stages of systematic and policies applied in the process of people development based on the company's needs for labor in the activities undertaken. Obstacles that occur during the human resource development a rise more dominant from the internal